2006
DOI: 10.1002/cncr.22388
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic significance of perineural invasion in prostatic cancer biopsies

Abstract: Men with clinically localized prostate cancer are faced with a wide range of treatment options, and only Gleason grading is universally used as a histopathological prognostic factor for this disease. The significance of perineural invasion in diagnostic biopsies is controversial. Opinion about whether or not it should influence treatment decisions is currently almost equally divided. To address this, the authors performed a systematic review of studies that examine the association between perineural invasion a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
92
1
5

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(99 citation statements)
references
References 45 publications
(244 reference statements)
0
92
1
5
Order By: Relevance
“…The previously described, 27 overarching, comprehensive search strategy to identify all articles relevant to prostate cancer and pathology was updated to the end of March 2007 and was extended to include Scopus in addition to MEDLINE, Embase, and the Web of Knowledge. To search for additional studies, hand searching of relevant journals was undertaken, and the reference lists of retrieved articles were scrutinized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The previously described, 27 overarching, comprehensive search strategy to identify all articles relevant to prostate cancer and pathology was updated to the end of March 2007 and was extended to include Scopus in addition to MEDLINE, Embase, and the Web of Knowledge. To search for additional studies, hand searching of relevant journals was undertaken, and the reference lists of retrieved articles were scrutinized.…”
Section: Methodsmentioning
confidence: 99%
“…Structured data extraction was performed as described previously to define the study design and outcomes reporting 27 that allowed comparison between studies. Data specific to the question under scrutiny included the definition of microfocal carcinoma and the number of biopsy cores obtained, because the diagnosis of microfocal carcinoma may have different implications, depending on how extensively the prostate was sampled.…”
Section: Methodsmentioning
confidence: 99%
“…Although some authors have asserted that the detection of PNI in needle biopsy specimens might increase risk of extra-prostatic extension, this issue is still debatable. In their systematic review, Harnden et al (7) investigated the importance of the detection of PNI in cases with postoperative and postradiotherapeutic recurrences and demonstrated its significant prognostic value, especially in patient subgroups defined based on serum PSA levels and GS. They also indicated that patients whose biopsy specimens had evidence of PNI were not suitable for watchful waiting and they required early therapeutic intervention.…”
Section: Discussionmentioning
confidence: 99%
“…In prostate cancer PNI is common and is seen in 7%-43% of biopsies 11 and in 77%-93% of prostatectomy specimens from patients in whom previous biopsy was positive for PNI. 4,13 Its prognostic value is still controversial, but in more recent studies primarily focused on PNI, it appears to be an independent prognostic factor associated with decreased survival and increased recurrence rate.…”
Section: Discussionmentioning
confidence: 99%